Sensomics evaluation of sun drying for reducing the bitterness and astringency of crude Ancha tea - Zhibin Ye; Wenjing Huang; Zhenbin Chen; Jixin Zhang; Chenxin Hu; Huan Zhou; Qian Xu; Jingming Ning (npj Science of Food)
Abstract Drying plays a crucial role in shaping tea’s quality. This study investigated the effects of sun drying, hot-air drying, and combined drying on the taste profile of crude Ancha tea (CAT) by using sensory analysis and metabolomics methods. One-way analysis of variance and multivariate statistical analysis identified 33 key differential metabolites in CAT, including six substances with a dose over threshold (Dot) > 1 that contributed to bitterness and astringency: (−)-epicatechin gallate, (−)-epigallocatechin gallate, kaempferol-3-glucoside, quercetin-3-glucoside, myricetin-3-galactoside, and kaempferol-3-rutinoside. Sun drying reduced the levels of (−)-epicatechin gallate, (−)-epigallocatechin gallate, and kaempferol-3-rutinoside but increased the levels of kaempferol-3-glucoside, quercetin-3-glucoside, and myricetin-3-galactoside, thereby reducing the bitterness and astringency of CAT. Taste addition experiments confirmed that these six target compounds were the main contributors to the differences in bitterness and astringency between the CAT samples prepared using different drying methods. Moreover, the experiments demonstrated that caffeine significantly enhanced the intensity of bitterness.